The Impact of Marketing Mix and Destination Image on Revisit Intention: Mediation by E-WOM and Tourist Satisfaction through TikTok - Alam, Salman Ramadan Nur; Widiyanesti , Sri; Iskamto , Dedi (Asean International Journal of Business, 2025)
This research investigates how the Marketing Mix and Destination Image impact Revisit Intention at Shelter Galunggung, mediated by eWOM (electronic Word of Mouth) and Customer Satisfaction. Data from 385 respondents were gathered via a Google Form questionnaire and analyzed using descriptive statistics such as mean, median, mode, percentile, decile, and quartile. The study employs a combined descriptive and causal analysis approach to elucidate the interrelationships among variables and their effects on research outcomes. Utilizing Structural Equation Modeling (SEM) with Partial Least Squares (PLS), the research addresses the complex relationships and non-normal data distributions typical in survey-based studies. Shelter Galunggung, situated in the wilderness beneath Indonesia's Mount Galunggung, is renowned for its natural ambiance, depicted in its iconic logo that highlights the unique environment and appeal to visitors. By employing an objective and quantifiable approach, this study aims to provide a precise understanding of the factors influencing Revisit Intention in the tourism industry, specifically at Shelter Galunggung. The anticipated findings are poised to contribute significant insights into the drivers behind customers' decisions to revisit destinations. This research holds potential to offer actionable recommendations for marketers and business owners within the tourism sector, facilitating strategic improvements in customer satisfaction and retention strategies.